The Relationship of Breakfast and Hemoglobin Levels in Adolescent Girls at SMP Negeri 1 Tapa - Nur Sabrina Aisya Putri Radjak; Sitti Rahma; Andi Mursyidah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to determine the relationship between breakfast and hemoglobin levels in adolescent girls in the SMP Negeri 1 Tapa area. This study is a quantitative research with descriptive correlation analysis using a cross sectional approach. Based on the results of a study involving 68 respondents, it shows that most young women have breakfast habits in the adequate category, which is as many as 40 respondents (58.8%). The students who were in the breakfast category were good at 18 respondents (26.5%), while the breakfast category was less than 10 respondents (14.7%). In the examination of hemoglobin levels, it was found that the majority of female students experienced low hemoglobin levels, namely 46 respondents (67.6%). Meanwhile, female students with normal hemoglobin levels amounted to 22 respondents (32.4%). The results of the analysis using the Chi-square test obtained a value of p = 0.047, which shows a significant relationship between breakfast habits and hemoglobin levels in adolescent girls at SMP Negeri 1 Tapa.